2014
DOI: 10.1139/apnm-2013-0034
|View full text |Cite
|
Sign up to set email alerts
|

The performance effect of early versus late carbohydrate feedings during prolonged exercise

Abstract: The purpose of this study was to determine how the timing of isoenergetic carbohydrate feedings during prolonged cycling affects performance in a subsequent 10-km cycling time trial. Recreationally trained male cyclists (n = 8; age, 34.5 ± 8.3 years; mass, 80.0 ± 6.3 kg; body fat, 16.0% ± 3.8%, peak oxygen uptake, 4.54 ± 0.42 L·min(-1)) completed 4 experimental trials consisting of cycling continuously for 2 h at 62.4% ± 1.9% of peak oxygen uptake, followed immediately by a self-paced 10-km time trial. The 4 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…When carbohydrate was ingested more frequently, performance was improved. Two contrasting papers that operate as extensions of this work include work by Schweitzer et al [ 51 ] who concluded that preferentially delivering carbohydrate during the first or second half of a controlled cycling exercise bout offered no enhancement of performance, while a similar study design by Heesch and colleagues [ 52 ] indicated that providing carbohydrate consistently throughout or in the latter half of a 2-h cycling exercise bout at 62% of peak power decreased the time it took to cover a prescribed distance (10-km) while cycling. It is important to realize that key differences such as the duration of the exercise bout, the nature of the performance assessment (fixed distance vs. time-to-exhaustion) and amount of carbohydrate that was delivered all differed between these studies and can help to explain the differences in outcomes being reported.…”
Section: Introductionmentioning
confidence: 99%
“…When carbohydrate was ingested more frequently, performance was improved. Two contrasting papers that operate as extensions of this work include work by Schweitzer et al [ 51 ] who concluded that preferentially delivering carbohydrate during the first or second half of a controlled cycling exercise bout offered no enhancement of performance, while a similar study design by Heesch and colleagues [ 52 ] indicated that providing carbohydrate consistently throughout or in the latter half of a 2-h cycling exercise bout at 62% of peak power decreased the time it took to cover a prescribed distance (10-km) while cycling. It is important to realize that key differences such as the duration of the exercise bout, the nature of the performance assessment (fixed distance vs. time-to-exhaustion) and amount of carbohydrate that was delivered all differed between these studies and can help to explain the differences in outcomes being reported.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 8.Forest plot shows the effects (red square symbol) of experimental carbohydrate supplementation as compared to a control on exercise outcome for 112 interventions[49][50][51][52][53]78,[80][81][82][83][84][85][86][87][88][89][90][91][92][94][95][96][97][98][99][100][101][102][103][104][105][106][107]109,110,[112][113][114][115][117][118][119]122,124,[129][130][131][132][133][134]…”
mentioning
confidence: 99%